Seasonal dynamics of the bryophytes cover on dump of sulfur extraction (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
49 bryophytes species belonging to 2 divisions, 3 classes, 8 orders, 17 families, 32 genera have been found on the territory of sulphur mining dump. Taxonomic, ecological and biomorphological structure of bryophytes have been analyzed, their life strategies have been determined. Seasonal changes in the projective cover and biomass of dominant mosses species have been investigated. The obtained data testify the important role of bryophytes in restoring vegetation cover on the devastated territories of sulphur extraction.
Keywords: bryophytes, ecological groups, life forms, life strategies, projective cover, biomass, dump of sulfur deposit.